Tax coordination in a cross-hauling model: Conflict or harmony of interest? - Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
The paper analyzes strategic commodity taxation in a model with trade in a single private good which is simultaneously imported by consumers of a high-tax region and exported by its producers. Conditions for the existence of a Nash equilibrium are given and an asymmetry is introduced through different preferences for public goods. Two tax coordination measures are discussed, a minimum tax rate and a coordinated increase in the costs of cross-border shopping. It is shown that tax coordination generally benefits the high-tax country while the low-tax region will gain only if the intensity of tax competition is high in the initial equilibrium or if governments are price-sensitive towards the effective marginal costs of public good supply.
Keywords: 330; Steuerharmonisierung; Steuerwettbewerb; Verbrauchsteuer; Grenzüberschreitender Verkehr; Öffentliche Güter; Wohlfahrtsanalyse; Theorie